SISTEM INFORMASI GEOGRAFIS PEMETAAN LOKASI PUSKESMAS MENGGUNAKAN GOOGLE MAPS API DI KABUPATEN BADUNG - I Wayan Widi Karsana; Gede Surya Mahendra (Universitas Nusa Cendana, 2021)
The Badung Regency Government through the Health Office implements a comprehensive health service program for the community. Health service facilities and infrastructure for the community are continuously improved to meet public health services including the development of community health centers (puskemas). The Puskesmas in the Badung district stated that there are 13 units scattered in various areas. Several problems have arisen where the community cannot see the location of the nearest puskesmas if there is an emergency such as an accident. The solution is offered to overcome the problems that arise by designing and building a geographic information system for the location map of the health center using the Google Maps API for coordinating information on the location of the health center using a map from Google. The community is expected to be able to see the location of the closest puskesmas and to be able to get information about addresses and telephone numbers that can be contacted through the system. This Geographical Information System uses the waterfall model in system development from analysis, design, design, coding, implementation and system testing. The results of the design and implementation of the geographic information system for the location of the Badung district health center can help the community to see and find the location of the nearest puskesmas so that they can more quickly assist in handling in an emergency situation.